Laboratory observations of flow and sediment transport induced by plunging regular waves. Issue 11 (19th November 2013) - Sumer, B. Mutlu; Guner, H. Anil Ari; Hansen, Nilas Mandrup; Fuhrman, David R.; Fredsøe, Jørgen
<x xml:space="preserve">Abstract</x> [1] Two parallel experiments involving the evolution and runup induced by plunging regular waves near the shoreline of a sloping bed are considered: (1) a rigid‐bed experiment, allowing direct (hot film) measurements of bed shear stresses and (2) a sediment‐bed experiment, allowing for the measurement of pore‐water pressures as well as observation of sediment suspension and bed morphological changes. Both experiments utilize the same initial bed profile and wave forcing. The experiments show that the mean bed shear stresses experienced onshore of incipient breaking are amplified by nearly a factor of 2 relative to prebreaking conditions, whereas their corresponding turbulent fluctuations are amplified even more strongly, by a factor of 5–6. The plunging processes lead to a series of vortices, whose formation may be explained as the result of shear layer instability. Measurements show that these vortices can significantly enhance peaks in the offshore‐directed bed shear stresses. Moreover, near‐bed pore pressure measurements indicate that these vortices cause large upward‐directed pressure gradients, which in turn produce a corresponding series of suspended sediment plumes shoreward of the initial breaking event. These findings are related to the induced morphological changes over both short and long time scales. The present results are also compared and contrasted with previous experiments utilizing a similar methodology, but involving plunging solitary waves.